Prolonged viral pneumonia and high mortality in COVID-19 patients on anti-CD20 monoclonal antibody therapy - Feuth, Eeva (SPRINGER, 2025)
Purpose
In clinical practice, we observed an apparent overrepresentation of COVID-19 patients on anti-CD20 monoclonal antibody therapy. The aim of this study was to characterize the clinical picture of COVID-19 in these patients.
Methods
All adult patients from Turku University Hospital, Turku, Finland, with COVID-19 diagnosis and/or positive SARS-CoV-2 PCR test result up to March 2023, and with anti-CD20 therapy within 12 months before COVID-19 were included. Data was retrospectively obtained from electronic patient records.
Results
Ninety-eight patients were identified. 44/93 patients (47.3%) were hospitalized due to COVID-19. Patients with demyelinating disorder (n = 20) were youngest (median age 36.5 years, interquartile range 33-45 years), had less comorbidities, and were least likely to be hospitalized (2/20; 10.0%) or die (n = 0). COVID-19 mortality was 13.3% in the whole group, with age and male sex as independent risk factors. Persistent symptoms were documented in 33/94 patients (35.1%) alive by day 30, in 21/89 patients (23.6%) after 60 days, and in 15/85 after 90 days (17.6%), mostly in patients with haematological malignancy or connective tissue disease. Prolonged symptoms after 60 days predisposed to persistent radiological findings (odds ratio 64.0; 95% confidence interval 6.3-711; p < 0.0001) and persistently positive PCR (odds ratio 45.5, 95% confidence interval 4.0-535; p < 0.0001). Several patients displayed rapid response to late antiviral therapy.
Conclusion
Anti-CD20 monoclonal antibody therapy is associated with high COVID-19 mortality and with a phenotype consistent with prolonged viral pneumonia. Our study provides rationale for retesting of immunocompromised patients with prolonged COVID-19 symptoms and considering antiviral therapy.